A novel benzoxazinone derivative YLT-LL-11 inhibits diffuse large B-cell lymphoma growth via inducing cell cycle arrest and apoptosis. Issue 10 (11th October 2019) - Peng, Cuiting; Sun, Changzhen; Wang, Ningyu; He, Yuanmin; Xu, Jixiang; Deng, Yongqiong; Gao, Lanyang; Zhong, Jianqiao; Xiong, Xia; Liu, Li
Abstract: Diffuse large B-cell lymphoma (DLBCL) is a clinically aggressive B-cell non-Hodgkin's lymphoma (NHL) with high treatment difficulty and high relapse rate. The bromodomain and extra-terminal (BET) proteins play significant roles in supporting the transcription of known DLBCL oncogene MYC, which provides a way for the development of targeted therapeutic agents to address this kind of malignant tumor. Here, we reported a novel benzoxazinone derivative YLT-LL-11 as potential BRD4 inhibitor and further investigated the biological activities against DLBCL. The results suggested that YLT-LL-11 inhibited cell growth against a panel of human hematopoietic malignancies cell lines in a dose- and time-dependent manner. In addition, flow cytometry and Western blotting assays showed that YLT-LL-11 inhibited the proliferation of a DLBCL cell line OCI-LY10 via inducing G0/G1 cell cycle arrest with regulation of the cyclin-dependent kinases (CDKs) expression. Furthermore, YLT-LL-11 facilitated OCI-LY10 cell apoptosis by up-regulation of pro-apoptotic protein BAX and down-regulation of anti-apoptotic protein Bcl-2. Taken together, these results revealed that BRD4 inhibitor YLT-LL-11 can down-regulate growth-associated transcription factors MYC in DLBCL thus resulted in cell growth inhibition and apoptosis.